Small Molecular Prodrug Amphiphile Self-Assembled AIE Dots for Cancer Theranostics - Yang, Xing; Luo, Yuan; Li, Sanpeng; Xu, Xiuli; Bao, Yingxia; Yang, Jiaming; Ouyang, Defang; Fan, Xingxing; Gong, Ping; Cai, Lintao (Frontiers in Bioengineering and Biotechnology, 2020)
A facile and simple one-step method was developed to fabricate small molecular prodrug amphiphile self-assembled organic dots CPPG with aggregation-induced emission (AIE) characteristics. With integration the advantages of AIE aggregates with strong emission and the cell-targeting capability of small molecular prodrug amphiphile CPPG, the as-prepared CPPG AIE dots can specifically target to cancer cells and inhibit the proliferation of the cancer cells with good biocompatibility photostability. Based on this universal method, a variety of versatile organic fluorescent nanoprobes with high brightness, specific recognition and clinical-transitional potential could be facilely constructed for biological therapeutics and imaging applications.